Correlation between the Internet addiction and affect score among medical students - N, Bhagyashree; Kiran Veerapaneni; Sai Sailesh Kumar Goothy (Asian Journal of Medical Sciences, 2023)
Background: The Internet has become an integral part of our day-to-day life. It is one of the most influential media in the modern era and incorrect usage might be harmful. About 90% of adolescents use it for acquiring information. Its development has given lots of chance for exchange of information, communication, and social interactions. One of the major public health concerns accompanied with it is the internet addiction. Aims and Objectives: The objective of the study was to assess and to correlate the affect scores and Internet addiction test (IAT) score among medical college students using the positive and negative affect (NA) schedule scale and Young’s IAT. Materials and Methods: This cross-sectional study was conducted among the 1st-year and 2nd-year medical students to assess the Internet addiction and positive and NA score. They were asked to fill separate questionnaires. Results: The result showed that the duration spent in viewing the Internet and IAT score had a significant negative correlation with the positive affect score (P=0.001) and significant positive correlation with NA score (P≤0.001). Conclusion: Intervention measures should be taken to minimize the effects of internet addiction on affect score. Awareness about harmful effects of excess Internet use should be provided so as to enhance the academic performance of students.